EFFECT OF DISCIPLINE OF WORK AND ORGANIZATIONAL COMMITMENT TO THE PERFORMANCE OF PERSONALITY ON TEACHER TEACHER COMPETENCE mediated SMP N 2 CITY AND SMP N 39 Semarang - Sukati, 1252020020 (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to examine and describe the effect of ( 1 ) Discipline working towards personal competence , ( 2 ) organizational commitment to personal competence , ( 3 ) Discipline of work on teacher performance , ( 4 ) organizational commitment to teacher performance , ( 5 ) the personality Competence teacher performance , ( 6 ) Discipline mediated work against knerja teachers personal competence , ( 7 ) organizational commitment mediated the performance of personal competence is teacher .research of census research throughout the teacher of SMP N 2 and SMP N 39 Semarang , amounting to 100 people were taken as respondents the instrument used for data collection was a questionnaire using a scale that has been tested and Liketr qualify the validity and reliability of the factor analysis and Cronbachs Alpha , as well as the classic assumption test . The technique of data analysis using the SPSS model testing . Multiple linear regression analysis , including R2 test , F test , hypothesis testing ( t test ) , as well as mediation test . The research proves that : ( 1 ) working Discipline significant positive effect on personal competence , ( 2 ) organizational commitment is significant positive effect on personal competence , ( 3 ) job working Discipline significant positive effect on teacher performance , ( 4 ) a significant positive effect of organizational commitment on teacher performance , ( 5 ) personality Competence significant positive effect on teacher performanceÂ  , ( 6 ) Competence not personality mediate the effect of labor discipline on teacher performance ( 7 ) Competence does not mediate the effect of personality on the performance of teachers organizational commitment . Keywords : Work discipline , organizational commitment , competence and performance of the teacher s personality